2008
DOI: 10.1063/1.2959735
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of liver cancer cells in vitro by a plasma needle

Abstract: A plasma needle using a dielectric barrier discharge reactor at atmospheric pressure with a funnel-shaped nozzle was developed. The preliminary characteristics of the plume and applications to the ablation of cultured human hepatocellular carcinoma (HCC) BEL-7402 cell line were presented. The effect of oxygen, which was injected into argon plasma afterglow region through a steel tube, was studied. The efficiency of argon-oxygen plasma depends sensitively on the oxygen concentration in argon plasma. Large diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 18 publications
5
87
0
Order By: Relevance
“…But also emerging application areas like plasma healthcare can be approachable by the usage of non-LTE plasmas (Stoffels, 2007;Kong et al, 2009;Lloyd et al, 2010;Laroussi, 2009;Fridman et al, 2008). Thus, plasma treatment of cancer cells (Kim, Kim, Park, Jeon, Seo, Iza and Lee, 2009;Vandamme et al, 2010;Zhang et al, 2008), living human cells (Tümmel et al, 2007;Stoffels et al, 2008;Yonson et al, 2006), prevention of nosocomial infections and the therapy of infected wounds (Fridman et al, 2008;Isbary et al, 2010) as a few examples are in the ongoing research focus.…”
Section: Plasma Classificationmentioning
confidence: 99%
“…But also emerging application areas like plasma healthcare can be approachable by the usage of non-LTE plasmas (Stoffels, 2007;Kong et al, 2009;Lloyd et al, 2010;Laroussi, 2009;Fridman et al, 2008). Thus, plasma treatment of cancer cells (Kim, Kim, Park, Jeon, Seo, Iza and Lee, 2009;Vandamme et al, 2010;Zhang et al, 2008), living human cells (Tümmel et al, 2007;Stoffels et al, 2008;Yonson et al, 2006), prevention of nosocomial infections and the therapy of infected wounds (Fridman et al, 2008;Isbary et al, 2010) as a few examples are in the ongoing research focus.…”
Section: Plasma Classificationmentioning
confidence: 99%
“…It has been reported that plasma induces power-and timedependent cell death in several cell lines (Montie et al, 2000;Stoffels et al, 2006;Zhang et al, 2008). A gas-only treatment (helium and oxygen) was used to exclude the gas effects of nonthermal atmospheric plasma.…”
Section: Effect Of Non-thermal Atmospheric Plasma On Cell Viabilitymentioning
confidence: 99%
“…Studies investigating the interaction of plasma jets with living cells have shown eradication of pathogens (Goree et al, 2006;Kolb et al, 2008;Stoffels et al, 2006), blood coagulation Kalghatgi et al, 2007;Kieft et al, 2005), tissue sterilization Shashurin et al, 2008), and the ablation of cultured liver cancer cells (Zhang et al, 2008). The effects of cold atmospheric plasma were shown to be due not to heat, but to active species, mainly oxygen/hydroxyl radicals and nitric oxide, generated in the plasma or in the tissue brought into contact with the plasma (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations